Autonomous Shipborne In Situ Reflectance Data in Optically Complex Coastal Waters: A Case Study of the Salish Sea, Canada - Wang, Ziwei; Costa, Maycira (Frontiers in Remote Sensing, 2022)
Present limitations on using satellite imagery to derive accurate chlorophyll concentrations and phytoplankton functional types arise from insufficient in situ measurements to validate satellite reflectance (Rrs(0+)). We installed a set of hyperspectral radiometers with solar tracking capability that permits autonomous operation (denoted as SAS-ST) on top of a commercial ferry to measure the in situ reflectance as the ferry crosses the Salish Sea Canada. Here, we present the SAS-ST installation and geometry of acquisition to allow for a clear view of the sea surface and avoid ship superstructure interference. Data processing, including ship superstructure perturbation correction, non-nadir viewing geometry correction, and data quality assurance for optimal in situ Rrs(0+), was conducted to ensure that data can be used to validate atmospheric correction of satellite-derived ocean Rrs(0+). The ship superstructure perturbation correction decreased the overall Rrs(0+) by 0.00055 sr-1 based on a black pixel assumption of the infrared band of the acquired lowest turbid water adapted from Hooker and Morel (2003). The BRDF correction using the inherent optical properties approach developed by Lee et al. (2011) lowered the spectral signal by ~5-10%, depending on the wavelength. The quality of the resulting reflectance was evaluated according to the quality assurance method developed by Wei et al. (2016), and ~92% of the acquired reflectance data matched well against the global database, indicating high quality.